Piperine Attenuates TBI-Induced Seizures via Inhibiting Cytokine-Activated Reactive Astrogliosis - Song, Yabei; Cao, Caiyun; Xu, Qiuyue; Gu, Simeng; Wang, Fushun; Huang, Xi; Xu, Shijun; Wu, Erxi; Huang, Jason H. (Frontiers in Neurology, 2020)
Peppers have been used in clinics for a long time and its major component piperine has been proved to be effective in the treatment of seizures. The purpose of this study was to investigate the effects of piperine on early seizures in mice after traumatic brain injury (TBI), and to explore the mechanism of the drug against the development on TBI. SPF-grade mice were randomly divided into 6 dietary groups for a week: control group, TBI group, 3 piperine group (low PPRD group with 10mg/kg PPR, medium PPRZ group with 20mg/kg PPR, and high PPRG group with 40mg/kg PPR) and positive control group (200mg/kg valproate). Except for the control group, all the other groups used Feeney free weight-falling method to establish the TBI of closed brain injury in mice, and the corresponding drugs were injected intraperitoneally for 7 days continuously after the brain injury. The results from behavior and EEG showed that piperine attenuated subthreshold dose of pentylenetetrazole (PTZ) induced seizures, compared with TBI group. Western blot results showed that the expression levels of inflammatory factors TNF-α, IL-1β were reduced by piperine. Immunostaining results showed that BDNF was also reduced by piperine, In addition, positive cell counts of astrocytic fibrillary acidic protein (GFAP) in Immuno-fluorescence (IF) showed that they were also reduced. Our data showed that piperine treatment can reduce the degree of cerebral edema, down-regulate the TNF-α, IL-1β and BDNF, decrease the reactivity of GFAP in the hippocampus, and inhibit TBI induced seizures.